Decompressive surgery in cerebral venous sinus thrombosis due to vaccine‐induced immune thrombotic thrombocytopenia. (5th March 2023) - Krzywicka, Katarzyna; Aguiar de Sousa, Diana; Cordonnier, Charlotte; Bode, Felix J.; Field, Thalia S.; Michalski, Dominik; Pelz, Johann; Skjelland, Mona; Wiedmann, Markus; Zimmermann, Julian; Wittstock, Matthias; Zanotti, Bruno; et al.
Abstract: Background and purpose: Cerebral venous sinus thrombosis due to vaccine‐induced immune thrombotic thrombocytopenia (CVST‐VITT) is an adverse drug reaction occurring after severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccination. CVST‐VITT patients often present with large intracerebral haemorrhages and a high proportion undergoes decompressive surgery. Clinical characteristics, therapeutic management and outcomes of CVST‐VITT patients who underwent decompressive surgery are described and predictors of in‐hospital mortality in these patients are explored. Methods: Data from an ongoing international registry of patients who developed CVST within 28 days of SARS‐CoV‐2 vaccination, reported between 29 March 2021 and 10 May 2022, were used. Definite, probable and possible VITT cases, as defined by Pavord et al. (N Engl J Med 2021; 385: 1680–1689), were included. Results: Decompressive surgery was performed in 34/128 (27%) patients with CVST‐VITT. In‐hospital mortality was 22/34 (65%) in the surgical and 27/94 (29%) in the non‐surgical group ( p  < 0.001). In all surgical cases, the cause of death was brain herniation. The highest mortality rates were found amongst patients with preoperative coma (17/18, 94% vs. 4/14, 29% in the non‐comatose; p  < 0.001) and bilaterally absent pupillary reflexes (7/7, 100% vs. 6/9, 67% with unilaterally reactive pupil, and 4/11, 36% with bilaterally reactive pupils; p  = 0.023). Postoperative imaging revealed worsening of index haemorrhagic lesion in 19 (70%) patients and new haemorrhagic lesions in 16 (59%) patients. At a median follow‐up of 6 months, 8/10 of surgical CVST‐VITT who survived admission were functionally independent. Conclusions: Almost two‐thirds of surgical CVST‐VITT patients died during hospital admission. Preoperative coma and bilateral absence of pupillary responses were associated with higher mortality rates. Survivors often achieved functional independence.